Fabrication of speckle patterns by focused ion beam deposition and its application to micro-scale residual stress measurement. (21st July 2015) - Zhu, Ronghua; Xie, Huimin; Xue, Yunfei; Wang, Liang; Li, YanJie
Abstract: This paper deals with the characterization of influence parameters on the fabrication of speckle patterns using FIB deposition. In many manufacturing processes the presence of residual stress is disturbing, and can significantly affect the mechanical properties of materials and structures. Digital image correlation (DIC) is validated to be an effective approach for the determination of micro-scale residual stress under the dual-beam microscope (FIB-EB). Considering the high-quality micro-scale speckle pattern is the prerequisite in DIC measurement, the influence parameters on the deposited speckle patterns, such as the quality of the speckle template, total deposition time, ion beam current density, and dwell time, are primarily discussed. Moreover, in the measurement of residual stress, the integrated fabrication technique under the FIB-EB dual-beam system is also explained, covering the following steps: fabrication of the speckle pattern by FIB deposition, slot milling for stress release by FIB, high-resolution SEM imaging before and after stress release as well as the deformation analysis by DIC. As application, the optimized micro-scale speckle patterns are deposited on the surface of laser shock peened metallic glass, and the residual stress distribution on the sample surface is successfully measured.